Prevention of submicron aerosolized particle dispersion: evaluation of an aerosol box using a pediatric simulation model. (1st December 2022) - Tabone, Laurence; Rivest, Dominic; Levy, Arielle; Buyck, Michael; Jouvet, Philippe; Aubin, Carl-Eric; François, Tine; Robert, Etienne; Baudin, Florent
ABSTRACT: Background and Aim: The SplashGuard CG (SG) is a barrier enclosure developed to protect healthcare workers from SARS-CoV-2 transmission during aerosol-generating procedures. Our objective was to evaluate the protection provided by the SG against aerosolized particles (AP), using a pediatric simulation model of spontaneous ventilation (SV) and noninvasive ventilation (NIV). Methods: An aerosol generator was connected to the airways of a pediatric high-fidelity manikin with a breathing simulator. AP concentrations were measured both in SV and NIV in the following conditions: with and without SG, inside and outside the SG, with and without suction applied to the device. Results: In the SV simulated setting, AP peaks were lower with SG: 0.1 × 10 5 particles/L compared to without: 1.6 × 10 5, only when the ports were closed and suction applied. In the NIV simulated setting, AP peaks outside the SG were lower than without SG (20.5 × 10 5 particles/L), whatever the situation, without suction (14.4 × 10 5 particles/L), with suction and ports open or closed: 10.3 and 0.7 × 10 5 particles/L. In SV and NIV simulated settings, the AP peaks measured within the SG were much higher than the AP peaks measured without SG, even when suction was applied to the device. Conclusions: The SG seems to decrease peak AP exposure in the 2 ventilation contexts, but only with closed port and suction in SV. However, high concentrations of AP remain inside even with suction and SG should be used cautiously.